Gasochromic performance of WO3 nanorod thin films for low concentration H2 sensing - Yaacob, Mohd. Hanif; Ou, Jian Zhen; Oh, C.; Kang, J.; Sberveglieri, Giorgio; Wlodarski, Wojtek (Elsevier, 2011)
Absorbance response of tungsten trioxide (WO3) nanorod thin films coated with palladium (Pd) towards hydrogen (H2) was investigated. WO3 nanorods were deposited onto quartz substrates via pulsed laser deposition (PLD) technique. Highly homogeneous arrays of nanorods in the sizes of 30 - 80 nm were observed. Subsequently, 25 Å Pd was deposited onto films via dc sputtering. The Pd/WO3 nanorod thin films exhibited excellent gasochromic response when measured in the visible-NIR range (400 – 1000 nm). As low as 0.06% H2 concentration was clearly sensed. A significant reversible absorbance change and fast recovery (<2 min) were observed when the films were exposed to H2 with different concentrations.